Analisis Biaya Pemupukan Tanaman Belum Menghasilkan Kelapa Sawit (Elaeis Guineensis Jacq) Di Kebun Ibunda PT Putri Hijau - Sinaga, Nurkhotimah; Gultom, Ferdian Dwinata; Lubis, Fadli Akbar (Jurnal Riset AKuntansi dan Bisnis, 2024)
The fertilization cost component is a high cost component, it can reach 40-60% of the total plant maintenance costs as a whole or around 24% of the total production costs.  This research aims to determine the amount and composition of fertilization costs for immature oil palm plants in PT Putri Hijau's, Ibunda plantation and to determine the fertilization costs per hectare and fertilization costs. The research sample of Immature Plants was in Afdeling II with a population of 68,871 trees, with a Stand per Hectare (SPH) or planting density of 131 trees/ ha for the 2019 planting year. The research method is a descriptive method.  The collected data is then analyzed, then described systematically so that it is easy to understand.   From the research results From the results of the study, it was concluded that the cost of fertilizing oil palm TBM in the Ibunda Plantation of PT Putri Hijau was Rp 16,329,252,576 (for 3 years of TBM) with the composition of Material Costs of 95.34%, Labor Costs 4.57%, and Transportation Costs 0.09%. The cost of fertilizing oil palm TBM in the Ibunda Plantation of PT Putri Hijau was Rp 31,000,000 per hectare. The cost of fertilizing Immature Oil Palm Plants in the Ibunda Plantation was Rp 238,000 per tree